A Survey on Performance Optimization of Cache Memory in the Individual Nodes of Wireless Sensor Networks - V, Amulya; KG, Mohan; HS, Ramesh Babu (International Journal of Computer Sciences and Engineering, 2025)
The wireless networks are constrained networks with limited battery backup and memory. The nodes in the Wireless Sensor Network use memory buffers to keep track of the sequence number of the Transport layer segments. This helps to resend the packets during the time of packet loss. The fast retransmission of the lost packets is done by nodes of Wireless Sensor Network with the help of fastest form of memory called as cache memory. This helps to achieve reliability. Understanding the working of cache memory in fulfilling such a great responsibility is a challenge. The survey has been conducted to understand the different types of processors and memories that could be used in the nodes of wireless sensor networks. An overview of optimization methods on cache memory and cache mapping mechanisms to improve the performance of the cache are also studied.